M. I. Finley, On a perdu la guerre de Troie. Propos et polémiques sur l´Antiquité, París, Les Belles Lettres, 19932, 236 pp. ISBN 2-251-38002-7 (Minerva. Revista de Filología Clásica, 2019)
Reseña de M. I. Finley, On a perdu la guerre de Troie. Propos et polémiques sur l´Antiquité, París, Les Belles Lettres, 19932, 236 pp. ISBN 2-251-38002-7